2020
DOI: 10.1038/s41598-020-75566-9
|View full text |Cite
|
Sign up to set email alerts
|

Decline of six native mason bee species following the arrival of an exotic congener

Abstract: A potential driver of pollinator declines that has been hypothesized but seldom documented is the introduction of exotic pollinator species. International trade often involves movement of many insect pollinators, especially bees, beyond their natural range. For agricultural purposes or by inadvertent cargo shipment, bee species successfully establishing in new ranges could compete with native bees for food and nesting resources. In the Mid-Atlantic United States, two Asian species of mason bee (Osmia taurus an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 38 publications
0
62
0
Order By: Relevance
“…It is known that invasive pollinators have a strong negative effect on congener native species (Inoue et al, 2008;Morales et al, 2013). For example, LeCroy et al (2020) have recently demonstrated how the presence of a non-native mason bee Osmia taurus leads to declines in the abundance of six native congener species (Osmia sps.). Our study shows that an invasive pollinator not only can drastically affect congener species interactions (B. dalhbomii and B. ruderatus), but also reduces direct and indirect ecological interactions of native non-congener species (P. albopilosa, M. gayi and R. mutabilis).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that invasive pollinators have a strong negative effect on congener native species (Inoue et al, 2008;Morales et al, 2013). For example, LeCroy et al (2020) have recently demonstrated how the presence of a non-native mason bee Osmia taurus leads to declines in the abundance of six native congener species (Osmia sps.). Our study shows that an invasive pollinator not only can drastically affect congener species interactions (B. dalhbomii and B. ruderatus), but also reduces direct and indirect ecological interactions of native non-congener species (P. albopilosa, M. gayi and R. mutabilis).…”
Section: Discussionmentioning
confidence: 99%
“…These species have become established in the eastern U.S. and because they share similar host‐plant ranges and nesting requirements with the native Osmia lignaria lignaria and other Osmia species, there has been concern that these introduced species might be competing with and mediating population declines in native species. Recent research suggests that this may be the case (LeCroy et al ., 2020; but see also Centrella, 2019). Other species have also been introduced but have not yet established outside of their native ranges.…”
Section: Introductionmentioning
confidence: 94%
“…LeCroy et al . (2020) needed 15 years data to report on precipitous declines of several species of Osmia bees associated with two invasive congeners; actions to reverse these declines were not proposed, nor are any realistic ones immediately evident. Powney et al .…”
Section: What Surveillance Cannot Domentioning
confidence: 99%
“…Other recent field studies of bees attest to the length of time required to establish significant trends. LeCroy et al (2020) needed 15 years data to report on precipitous declines of several species of Osmia bees associated with two invasive congeners; actions to reverse these declines were not proposed, nor are any realistic ones immediately evident. Powney et al (2019) used Bayesian analysis of 33 years of haphazardly gathered survey data in the United Kingdom to report declines in patch occupancy rates for 32% of solitary bee species; no testable hypotheses were offered to explain these declines nor were actions proposed to reverse them.…”
Section: What Surveillance Cannot Domentioning
confidence: 99%